Polymerisation and export of alginate in Pseudomanas aeruginosa : functional assignment and catalytic mechanism of Alg8/44 : a thesis presented to Massey University in partial fulfilment of the requirement for the degree of Doctor of Philosophy in Microbiology - Remminghorst, Uwe (Massey University, 2007)
Alginate biosynthesis is not only a major contributor to pathogenicity of P. aeruginosa but also an important factor in colonization of adverse environmental habitats by biofilm formation. The requirement of proteins Alg8 and Alg44, encoded by their respective genes in the alginate biosynthesis gene cluster, for alginate biosynthesis of P. aeruginosa was demonstrated, since deletion mutants were unable to produce or polymerise alginate. AlgX deletion mutants failed to produce the alginate characteristic mucoid phenotype, but showed low concentrations of uronic acid monomers in the culture supernatants. Complementation experiments using PCR based approaches were used to determine the complementing ORF and all deletion mutants could be complemented to at least wildtype levels by introducing a plasmid harbouring the respective gene. Increased copy numbers of Alg44 did not impact on the amount of alginate produced, whereas increased copy numbers of the alg8 gene led to an at least 10 fold stronger alginate production impacting on biofilm structure and stability. Topological analysis using reporter protein fusions and subsequent subcellular fractionation experiments revealed that Alg8 is located in the cytoplasmic membrane and contains at least 4 transmembrane helices, 3 of them at its C terminus. Its large cytosolic loop showed similarities to inverting glycosyltransferases and the similarities were used to generate a threading model using SpsA, a glycosyltransferase involved in spore coat formation of B. subtilis, as a template. Site-directed mutagenesis confirmed the importance of identified motifs commonly detected in glycosyltransferases. Inactivation of the DXD motif, which has been shown to be involved in nucleotide sugar binding, led to loss-offunction mutants of Alg8 and further replacements revealed putative candidates for the catalytic residue(s). Contradicting the commonly reported prediction of being a transmembrane protein, Alg44 was shown to be a periplasmic protein. The highest specific alkaline phosphatase activity of its fusion protein could be detected in the periplasmic fraction and not in the insoluble membrane fraction. Bioinformatical analysis of Alg44 revealed structural similarities of its N terminus to PilZ domains, shown to bind cyclic-di-GMP, and of its C terminus to MexA, a membrane fusion protein involved in multi-drug efflux systems. Thus, it was suggested that Alg44 has a regulatory role for alginate biosynthesis in bridging the periplasm and connecting outer and cytoplasmic membrane components. AlgX was shown to interact with MucD, a periplasmic serine protease or chaperone homologue, and is suggested to exert its impact on alginate production via MucD interaction. In vitro alginate polymerisation assays revealed that alginate production requires protein components of the outer and cytoplasmic membrane as well as the periplasm, and these data were used to construct a model describing a multi-enzyme, membrane and periplasm spanning complex for alginate polymerisation, modification and export.
Keywords: Pseudomonas aeruginosa; Alginates; Biosynthesis; Fields of Research::270000 Biological Sciences::270300 Microbiology